Controllability problems for the string equation - Fardigola, L. V.; Khalina, K. S. (Ukrains’kyi Matematychnyi Zhurnal, 2007)
For the string equation controlled by boundary conditions, we establish necessary and sufficient conditions for 0-and ε-controllability. The controls that solve such problems are found in explicit form. Moreover, using the Markov trigonometric moment problem, we construct bangbang controls that solve the problem of ε-controllability.